ANALISIS STANDAR PENILAIAN PENDIDIKAN PADA JENJANG PENDIDIKAN DASAR BERDASARKAN PERMENDIKBUDRISTEK NO. 21 TAHUN 2022 - Madhita Anjani, Parra; Gitasmara, Fanny Ramdhanissa; Jaya, Indra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In organizing quality and quality education, of course, the government has a rule, which is a reference for educational institutions. Educational assessment standards are a reference or guideline for educators, education units, and the government in carrying out assessments of student learning outcomes. The literature study method is used to analyze the assessment standards and provide an overview for educators in understanding the assessment standards in Permendikbudristek No. 21 of 2022. The results of this analysis are expected to help educators to understand the outline of the latest assessment standards and provide insight into the success of the assessment process at the elementary school level. Assessment of learning outcomes is divided into formative and summative, which aims to provide feedback to students and evaluate their achievements at the end of the learning period. Reporting of assessment results should be informative and understood by all stakeholders and provide follow-up recommendations for further development.